di- Analisis Pemahaman Terhadap Penggunaan Imbuhan di- Pada Kalangan Masyarakat: Pemahaman Penggunaan Imbuhan di- Pada Kalangan Masyarakat - Zuhrufunnisa, Nida (Universitas Negeri Surabaya, 2024)
This study aims to analyze people's understanding of distinguishing between di- as a prefix and di- as a preposition. The method used in this study is a quantitative method with a survey research process using questions. The population in this study is all people and is not determined by age. Based on 41 respondents, the results of the analysis show that the percentage of correct answers to all questions is 73.6% and the percentage of wrong answers to all questions is 26.3%. It can be concluded that the cause of errors in the use of di- affixes in the community is caused by ignorance of language structures, standard word systematics, and little awareness of the use of good and correct Indonesian. Keywords: affixes, language structure, people understanding, prefix, preposition